STRATEGI PESANTREN TEBUIRENG MENGATASI BUTA AKSARA DI DESA WONOSALAM - Syarif Abdurrahman; Robith Fahmi (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
Al-Qur'an is the holy book of Muslims. So that its adherents must be able to read the Qur'an. Teaching to read the Qur'an is an obligation for every parent to his child. However, not all parents have the ability to do that. One of them is experienced by the community in Wonosalam Village, Wonosalam District, Jombang Regency, East Java. The Tebuireng Islamic Boarding School through the Tebuireng Islamic Boarding School (LSPT) Social Institution, Mahad Aly Hasyim Asy'ari Tebuireng and sugarcane.co made efforts to eradicate illiteracy in the Qur'an. The Tebuireng Islamic Boarding School team assists the people of Wonosalam Village in learning to write and read the Qur'an every day